SHADOW AND VENTILATION ASPECT IN THE THERMAL PERFORMANCE OF PATTERNED BRICK FACADES - Faedhillah Rana, Zadha
The use of patterned brick façades remains popular, despite several studies indicating that environmental heating effects occur as a result of their material utilization. This research focuses on the effectiveness of solar shading and surface air flow turbulence induced by brick arrangements to achieve optimal thermal performance, particularly for east and west walls. Two brick arrangement patterns are considered (angles of 0°, 30°, 60°, and 90°), along with the concept of surface cooling due to turbulence induced by these brick arrangement patterns. This research was conducted through three approaches: 1) a mathematical approach to calculate the accumulation of shaded area and its impact on estimated wall- received radiation using Indonesian Meteorology, Climatology, and Geophysics Agency (BMKG) data in accordance with the solar angle of incidence, 2) Experimental laboratory approach was employed on two models exposed to the highest (30° angle pattern) and lowest (60° angle pattern) radiation to confirm the shading effect and convective cooling. Surface wall temperature at various brick arrangement positions (Ts °C), ambient air temperature (Ta, °C), radiation temperature (Tg °C), and air velocity at different positions of the brick arrangement pattern (v m/s) were measured. A brick wall model sized 1.15 x 1.2 m was utilized, subjected to radiation exposure from two 1000 W halogen lamps during a 4-hour heating phase (from 08:30 am to 12:30 pm) and a 4-hour cooling phase (from 12:30 pm to 04:30 pm). The convective cooling effect was measured in several wind directions (0°, 45°, 90°, 135°, and 180°). Temperature measurements were conducted using a data logger with Type T thermocouple sensors, possessing an accuracy of 0.2%+1°C, with 16 channels, recorded at 5-minute intervals, 3) The effectiveness of convective cooling was further studied by investigating the wind turbulence pattern on the surface of the brick arrangement using Computational Fluid Dynamics (CFD) software. Measurement results confirmed the calculations, showing that the 30° pattern had higher surface temperatures, specifically 1.33°C (external) and 1.66°C (internal), compared to the 60° pattern. The shading produced on the protrusions and ventilation holes also led to a reduction in maximum surface temperature by 4.16°C and a minimum of 0.37°C. Effective shading decreases the heat gain on the patterned masonry façade. Furthermore, the protrusions on the brick wall generate turbulence and a convective cooling effect of 6.03°C at a 60° angle, which is superior to the 30° angle pattern. The 60° angle pattern, which features a larger ratio of ventilation holes compared to the 30° angle pattern, results in a greater exchange of airflow, causing the air temperature behind the façade to reach 25.50°C to 25.80°C. This research